The Role of Physical Activity Behavior in the Mental Wellbeing of Vocational Education and Training Students: The PHIT2LEARN Study - Kirschner, Mara; Golsteijn, Rianne H. J.; van der Wurff, Inge S. M.; Savelberg, Hans H. C. M.; de Groot, Renate H. M. (Frontiers in Education, 2022)
A positive association has been found between physical activity and student mental wellbeing (SMW). This association has been mainly explored in secondary school and university students. Studies in vocational education and training (VET) are lacking, while VET students could especially benefit from exploring this association since research shows that VET-students, who often come from low SES households, are prone to low SMW. Low SMW can result in higher school dropout rates and long-term negative effects like unemployment, social exclusion, and impoverishment. The aim of the current study is to explore the association between total PA as well as different physical activity behaviors (PAB, i.e., moderate to vigorous intensity (MVPA), low intensity (LPA), and sedentary behavior (SB)) and SMW in the VET setting. In this cross-sectional observational study, students wore an ActivPAL3TM accelerometer for seven consecutive days to measure PAB. SMW was assessed using the Centre for Epidemiologic studies Depression Scale (CES-D) and the Rosenberg self-esteem questionnaire (RSE). Complete data for the analyses was obtained from 85 students. Multiple regression analyses showed a significant positive association between total PA and self-esteem and a significant negative association between total PA and depressive symptoms. Taking different PA intensities into account, there was a significant positive association between LPA and self-esteem and a significant negative association between LPA and depressive symptoms. No significant associations were found between MVPA and the outcome measures, although the associations aligned with the findings for LPA. High levels of SB were significantly associated with low self-esteem, however the associations between SB and depressive symptoms was not significant. The significant positive associations between LPA and SMW and the negative association between SB and self-esteem indicate that decreasing SB and increasing LPA could contribute to improved SMW. Future research should determine if these are causal relationships.